Drivers of Labor Force Participation in Advanced Economies: Macro and Micro Evidence - Francesco Grigoli; Zsoka Koczan; Petia Topalova (Global Labor Organization (GLO), 2018)
Despite significant headwinds from population aging in most advanced economies (AEs), labor force participation rates show remarkably divergent trajectories both across countries and across different groups of workers. Participation increased sharply among prime-age women and, more recently, older workers, but fell among the young and prime-age men. This paper investigates the determinants of these trends using aggregate and individual-level data. We find that the bulk of the dramatic increase in the labor force attachment of prime-age women and older workers in the past three decades can be explained by changes in labor market policies and institutions, structural transformation, and gains in educational attainment. Technological advances such as automation, on the other hand, weighed on the labor supply of prime-age and older workers. In light of the dramatic demographic shifts expected in the coming decades in many AEs, our findings underscore the need to invest in education and training, reform the tax system, reduce early retirement incentives, improve the job-matching process, and help individuals combine family and work life in order to alleviate the pressures from aging on labor supply.
Keywords: J11; J21; O33; 330; labor force participation; policies; technology; routinization